Evaluating The Impact Of Professional Caregiver Performance Factors On Outpatient Satisfaction - Kurniasari, Annisa; Istiqomah, Ermina; Sanyoto, Didik Dwi; Illiandri, Oski; Jun Chen, Hana W; Nugroho, Adi (Jurnal Kesehatan Manarang, 2025)
The performance of professional caregivers and patient satisfaction are closely interrelated and mutually influential. As a primary indicator of dental healthcare quality, patient satisfaction is shaped by the comparison between service expectations and the actual care received. Satisfaction increases with excellent performance and decreases with poor performance. This study analyzed the association between key performance factors—specifically promptness, attitude, and communication of professional caregivers—and patient satisfaction in the Outpatient Unit of Gusti Hasan Aman Dental and Oral Hospital. An analytic observational design with a cross-sectional approach was employed, involving 105 patients selected through accidental sampling. Chi-square tests revealed significant associations between attitude (p = 0.000) and communication (p = 0.000) in service and patient satisfaction. However, no significant association was found between promptness (p = 0.331) and patient satisfaction. Multiple logistic regression analysis further confirmed the importance of attitude (p = 0.016) and communication (p = 0.005) in service as factors related to patient satisfaction, with communication emerging as the most dominant factor (OR = 6.064; 95% CI: 1.711–21.490). The analysis also considered respondent characteristics such as age, gender, type of healthcare financing, and education level. In conclusion, attitude and communication in service were significantly associated with patient satisfaction, with communication being the most influential factor.